Implementation Of The Principle Of Immunity For Consular Posts Of The Sending State In The Receiving State - Pratiwi, Dian Khoreanita (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2024)
The consular representative building is an extraterritorial territory of the sending country, and the sending country has jurisdiction over that territory. The trespassing incident that occurred at the Indonesian Consular Post by unknown people in Melbourne during 2017 to 2020 period was a violation of existing immunity rights. Based on the concept of diplomatic immunity, the receiving state must protect foreign consular posts in its territory. The method used in this research is a normative juridical research method. The data used is secondary data. Data is presented qualitatively and analyzed descriptively. The results of this research are that trespassing and raising the Morning Star flag is a form of